DSB:Ce3+ scintillation glass for future. (13th February 2015) - Auffray, E; Akchurin, N; Benaglia, A; Borisevich, A; Cowden, C; Damgov, J; Dormenev, V; Dragoiu, C; Dudero, P; Korjik, M; Kozlov, D; Kunori, S; et al.
Abstract: One of the main challenges for detectors at future high-energy collider experiments is the high precision measurement of hadron and jet energy and momentum. One possibility to achieve this is the dual-readout technique, which allows recording simultaneously scintillation and Cherenkov light in an active medium in order to extract the electromagnetic fraction of the total shower energy on an event- by-event basis. Making use of this approach in the high luminosity LHC, however, puts stringent requirements on the active materials in terms of radiation hardness. Consequently, the R&D carried out on suitable scintillating materials focuses on the detector performance as well as on radiation tolerance. Among the different scintillating materials under study, scintillating glasses can be a suitable solution due to their relatively simple and cost effective production. Recently a new type of inorganic scintillating glass: Cerium doped DSB has been developed by Radiation Instruments and New Components LLC in Minsk for oil logging industry. This material can be produced either in form of bulk or fiber shape with diameter 0.3-2mm and length up to 2000 mm. It is obtained by standard glass production technology at temperature 1400°C with successive thermal annealing treatment at relatively low temperature. The production of large quantities is relatively easy and the production costs are significantly lower compared to crystal fibers. Therefore, this material is considered as an alternative and complementary solution to crystal fibers in view of a production at industrial scale, as required for a large dual readout calorimeter. In this paper, the first results on optical, scintillation properties as well as the radiation damage behaviour obtained on different samples made with different raw materials and various cerium concentrations will be presented.